Pengaruh Senam Tera Indonesia Terhadap Penurunan Tekanan Darah Pada Lansia Hipertensi Desa Pasar Melintang Kecamatan Lubuk Pakam - Evelyn Cristiana Sitinjak; Liza Agustu; Ronald Erwansyah (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Elderly is a condition characterized by a person's failure to maintain a balance against physiological stress conditions. Tera Indonesia Gymnastics is a physical and mental exercise, combining movements of body parts with breathing techniques and rhythms through concentration of thoughts that is carried out regularly, harmoniously, correctly and continuously. The benefits of tera gymnastics are to improve and improve the condition and function of theheart and blood circulation, the respiratory system, the nervous system, food digestion, endocrine, muscle strength and endurance, muscle and joint flexibility, balance and coordination and metabolic processes. In addition to physical health, tera gymnastics also provides spiritual benefits, among others, maintaining stable self-control, reducing stress, training concentration, increasing sensitivity, fostering a sense of togetherness and kinship (Tera Gymnastics Community, 2009). Hypertension or high blood pressure disease is a disorder of the blood vessels resulting in the supply of oxygen and nutrients. This condition causes blood pressure in the arteries to increase and the heart has to work harder to meet these needs. diagnosed for a long time. The purpose of the study was to determine the effect of Indonesian tera gymnastics on reducing blood pressure in the elderly. This study used a one group pre-test-post-test research design with purposive sampling. The population in this study was Pasar Melintang Village, Lubuk Pakam District, which amounted to 12 people. Based on the Wilcoxon test, a significance value or p value = 0.002 (p <0.05) was obtained. So there is an effect of Indonesian tera gymnastics on reducing blood pressure in the elderly with hypertension in Pasar Melintang Village. Keywords: Tera Gymnastics, Elderly, Lowering Blood Pressure